INNOVATION IN THE TEACHING OF MATHEMATICS IN PRIMARY SCHOOL - Hyacintha, Sr. M. (SCHOOL SCIENCE, 2013)
The tribal children of the North East have been considered to be weak in mathematics. Many of them have even an aversion to or a fear of mathematics. Hence, maths is still an optional subject. However, experience has shown that these children are not less intelligent than others, that their aptitude for learning mathematics is the same as that of any other children in the rest of the country. The reason for their backwardness is that perhaps maths in schools here has not been handled as it should have been keeping in mind the tribal and rural background of the children.